THE CHARACTERIZATION OF ANGWA-KEDE LITHIUM ORE, KOKONA LOCAL GOVERNMENT AREA, NASARAWA STATE, NIGERIA - EBIKEMEFA EBIMOBOWEI CLINTON; RAMALAN ALIYU MOHAMMED; DUNGKA THOMAS (Innovare Journal of Social Sciences, 2024)
This research on the characterization of Angwa-Kede lithium ore, Kokona Local Government Area, Nasarawa State, Nigeria was carried out to identify the mineralogical content, elemental composition and the percentage content of lithium(Li) present in the ore. The research employed a systematic sampling method for obtaining lithium ore at various lithium mine pit and a weight sample of 100g was pulverized and analyzed using XRF for elemental characterization, XRD for identification of mineralogical phases and Flame Test analysis for identification of lithium concentration. The Flame Test result revealed that lithium concentration in the ore samples from the mining pit sites are found to be 0.3 and 1.85% respectively and thus are low grade lithium ores. The XRD results revealed that the mineral phases in the lithium ore are: quartz, albite and muscovite as major phases while petalite, lepidolite and spodumene are the minor phases in the matrix of the ore samples. XRF result shows that: Al, Cl, S, Si, Mg, K, Ca, Fe and P have percent significance values and are the major elements while others like Cu, Ti, Mo, Sr etc. have minor percent values (minor elements). Conclusively, a more appropriate beneficiation process can aid in increasing the grade of the ore and this can be beneficial to the nation’s metallurgical industry.